Macrophage targeting precision nanomedicine utilizing ROS-responsive metallozyme-loaded nanomicelle for enhanced treatment of gout-induced inflammation - Padmanaban Sathiyamoorthy; Shyam Vasvani; Sree Samanvitha Kuppa; Adityanarayan Mohapatra; Amal Babu; Yong-Yeon Jeong; Hong Yeol Yang; Jong Keun Seon; Chang-Moon Lee; In-Kyu Park (Science and Technology of Advanced Materials)
The excessive accumulation of monosodium urate crystals in joints leads to the pathological condition known as gout. While conventional treatments, which include Non-steroidal Anti-inflammatory Drugs, are available, their short half-life and low bioavailability limit their practical application. To overcome these limitations and leverage the Reactive Oxygen Species (ROS)-rich microenvironment, this study developed a novel ROS-responsive thioketal-linked hyaluronic acid-based micelle loaded with manganese oxide (HTO-MnO) for enhanced treatment. Following the synthesis of the HTO-MnO nanocomplex, the micelle was well characterized and the synthesized micelle were subjected to multiple tests to confirm their efficacy in reducing ROS. In addition, the in-vitro treatment of M1-polarized macrophages showed significant responses at both the gene and protein expression levels. Eventually, in-vivo analysis of the HTO-MnO nanoparticles was performed in the MSU-induced arthritis mouse model. The elevated ROS levels in the ankle joint of the mice triggered the release of MnO nanoparticles from the HTO micelles, suppressing the ROS levels and repolarizing macrophages to their M0 state, thereby effectively mitigating inflammation. This study demonstrates the potential of nanocomplex to reduce ankle swelling and intrinsic ROS levels by targeting M1 macrophages. The results highlight its precise therapeutic mechanism to alleviate inflammation and treat gouty arthritis.